2015
DOI: 10.1039/c4ra08887e
|View full text |Cite
|
Sign up to set email alerts
|

A first principles study of H2S adsorption and decomposition on a Ge(100) surface

Abstract: We employed density functional theory (DFT) calculations to examine the adsorption configurations and possible reaction paths for H2S on a Ge(100) surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This can be attributed to the build-up of Ge dangling bonds at Ge/dielectrics interface. It has been reported that the passivation of Ge surface by sulfide can result in Ge-S bonds and thus decrease the interface traps [12,16]. Moreover, it is suggested that H + protons generated at the anode by positive bias can drift to the Ge interface and break the passivated Ge-S bonds as shown in Fig.…”
Section: Bias Instabilitymentioning
confidence: 95%
See 2 more Smart Citations
“…This can be attributed to the build-up of Ge dangling bonds at Ge/dielectrics interface. It has been reported that the passivation of Ge surface by sulfide can result in Ge-S bonds and thus decrease the interface traps [12,16]. Moreover, it is suggested that H + protons generated at the anode by positive bias can drift to the Ge interface and break the passivated Ge-S bonds as shown in Fig.…”
Section: Bias Instabilitymentioning
confidence: 95%
“…Moreover, it is suggested that H + protons generated at the anode by positive bias can drift to the Ge interface and break the passivated Ge-S bonds as shown in Fig. 5 [12,27,30]. One possible reaction of the formation of an interface trap is shown in (7), Ge -S + 2 H +  Ge + + H2S…”
Section: Bias Instabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…On the fcc transition metal (100) surfaces, three high symmetry sites are considered for adsorption of H 2 S: top, bridge, and hollow sites (Figure 4a). On Fe, [98] Cu, [99] Pd, [100] and Au(100) [101] surfaces, molecular H 2 S prefers to adsorb on the top site, while on Ni, [102] Mo, [103] Rh, [104] and Ge(100) [105] surfaces, molecular H 2 S prefers to bind on the bridge site (Table 3). Former theoretical results show that the adsorption energies of molecular H 2 S on 3d metals (Fe, Ni, and Cu(100) surfaces) are in the range of À 0.50 to À 0.76 eV, while the adsorption energies of molecular H 2 S on 4d metals (Mo, Rh, and Pd(100) surfaces) are in the 100) surface with the adsorption energy of À 0.36 eV.…”
Section: H 2 S Adsorption and Dissociation On Low Index Fcc Transitio...mentioning
confidence: 99%